2020
DOI: 10.4187/respcare.06917
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Inhaler Technique

Abstract: BACKGROUND: This study was designed to evaluate the influence of gender on the inhaler technique of subjects on inhaler therapy and to determine the factors predicting the correct inhaler technique and a change of inhaler device. METHODS: A total of 568 adult subjects (276 male, 292 female) on inhaler therapy were included in this cross-sectional, observational study. Data on sociodemographic characteristics, inhaler therapy, subject-reported difficulties, and technician-reported errors in inhaler technique we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In some studies, the female (24) gender has been associated with a high risk of error of use of inhalers and with a high proportion of males that correctly use the inhales and who have a correct inhalation technique . However, other studies have (3) revealed a weaker performance among men concerning the correct manipulation of inhalers, while other studies did not identify any difference between the two genders (6,8,23).…”
Section: Original Papersmentioning
confidence: 79%
“…In some studies, the female (24) gender has been associated with a high risk of error of use of inhalers and with a high proportion of males that correctly use the inhales and who have a correct inhalation technique . However, other studies have (3) revealed a weaker performance among men concerning the correct manipulation of inhalers, while other studies did not identify any difference between the two genders (6,8,23).…”
Section: Original Papersmentioning
confidence: 79%
“…Gender is another disputed characteristic [10]. In most studies, female gender correlated with worse inhaler use, although not all studies confirmed this gender-based difference [91, 92]. Ocakli et al [92] demonstrated that women were often more aware of subjective inhaler use problems.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, female gender correlated with worse inhaler use, although not all studies confirmed this gender-based difference [91,92]. Ocakli et al [92] demonstrated that women were often more aware of subjective inhaler use problems. This characteristic does not require a specific assessment method.…”
Section: Gendermentioning
confidence: 99%
“…In our study patients sociodemographic characteristics like age and sex were not associated with incorrect inhaler using technique, though patients with lower educational attainment and socioeconomic condition reported to have higher rate of critical errors in using inhalers. However, elderly patients as well as female patients using inhalers were reported to face more di culties and make more errors in handling their devices in case of both MDI and DPI compared to their counterparts [13,27]. Besides, patients educational attainment was also reported as a signi cant predictor of inhaler using technique in different studies [28,29].…”
Section: Discussionmentioning
confidence: 99%